A Stepwise, Pilot Study of Bovine Colostrum to Supplement the First Enteral Feeding in Preterm Infants (Precolos): Study Protocol and Initial Results - Li, Yanqi; Juhl, Sandra M.; Ye, Xuqiang; Shen, René L.; Iyore, Elisabeth Omolabake; Dai, Yiheng; Sangild, Per T.; Greisen, Gorm O. (Frontiers in Pediatrics, 2017)
Study protocol: The optimal feeding for preterm infants during the first weeks is still debated, especially when mother´s own milk is lacking or limited. Intact bovine colostrum (BC) contains high amounts of protein, growth factors and immuno-regulatory components that may benefit protein intake and gut maturation. We designed a pilot study to investigate the feasibility and tolerability of BC as the first nutrition for preterm infants. The study was designed into three phases (A, B, C) and recruited infants with birth weights of 1000-1800 g (China) or gestational ages of 27+0 to 32+6 weeks (Denmark). In phase A, three infants were recruited consecutively to receive BC as a supplement to standard feeding. In phase B, seven infants were recruited in parallel. In phase C (not yet complete), forty infants will be randomized to BC or standard feeding. Feeding intolerance, growth, time to full enteral feeding, serious infections/NEC, plasma amino acid profile, blood biochemistry, and intestinal functions are assessed. This paper presents the study protocol and results from phases A and B. Results: Seven Danish and five Chinese infants received 22±11 ml∙kg-1∙d-1 and 22±6 ml∙kg-1∙d-1 BC for a median of 7±3 and 7±1 d which provided 1.81±0.89 and 1.83 ± 0.52 g∙kg-1∙d-1 protein, respectively. Growth rates until 37 wk or discharge were in the normal range (11.8±0.9 and 12.9±2.7 g∙kg-1∙d-1 in Denmark and China, respectively). No clinical adverse effects were observed. Five infants showed a transient hypertyrosinemia on d 7 of life. Discussion and conclusion: The three-phased study design was used to proceed with caution as this is the first trial to investigate intact BC as the first feed for preterm infants. BC supplementation appeared well tolerated and resulted in high enteral protein intake. Based on the safety evaluation of phases A and B, the randomized phase C has been initiated. When complete, the Precolos trial will document whether it is feasible to use BC as a novel, bioactive milk diet for preterm infants. Our trial paves the way for a larger randomized controlled trial on using BC as the first feed for preterm infants with insufficient access to mother´s milk.